Artificial Intelligence in FinTech and Its Implications for International Trade Efficiency - Ali Raza; Muhammad Ali (Inverge Journal of Social Sciences, 2026)
This study examined the role of Artificial Intelligence (AI) integration in Financial Technology (FinTech) and its implications for international trade efficiency. The research investigated how AI-driven mechanisms such as automated document processing, enhanced risk assessment, fraud detection, and compliance systems contributed to transaction cost reduction and overall trade performance. Using quantitative analysis, the study evaluated relationships among AI adoption, operational efficiency variables, and international trade efficiency. The findings revealed that AI integration significantly improved trade efficiency by accelerating cross-border payment processes, minimizing financial risks, and enhancing regulatory transparency. Transaction cost reduction emerged as a critical mediating factor linking AI-enabled FinTech innovations to improved trade outcomes. The results indicated that predictive analytics and machine learning models strengthened credit evaluation and fraud monitoring, thereby reducing uncertainty and information asymmetry in global trade transactions. The study concluded that AI-driven FinTech solutions functioned as strategic enablers of competitiveness in international markets by enhancing speed, reliability, and cost-effectiveness of trade finance operations. The findings provided empirical support for digital transformation theories within financial inter-mediation and highlighted the importance of supportive regulatory frameworks and digital infrastructure development. The study offered practical recommendations for policymakers and financial institutions seeking to leverage AI technologies to improve global trade efficiency. References Ali, A., & Rafiq-uz-Zaman, M. (2025). Institutional inertia vs. ethical innovation: A comparative analysis of AI governance at The Islamia University of Bahawalpur and Cambridge University Press. Contemporary Journal of Social Science Review, 3(4), 91–102. https://doi.org/10.63878/cjssr.v3i4.1695 Almoghayer, W. J. K., & Mahmoud, H. A. (2025). The adoption of cross-border payment systems: A comparative study of Belt and Road Initiative countries. Borsa Istanbul Review, 5(10), 011. https://doi.org/10.1016/j.bir.2025.10.011 (ScienceDirect) Arner, D. W., Barberis, J., & Buckley, R. P. (2017). FinTech, RegTech, and the reconceptualization of financial regulation. Northwestern Journal of International Law & Business, 37(3), 371–413. https://doi.org/10.2139/ssrn.2847806 Babina, T., Fedyk, A., He, A., & Hodson, J. (2023). Artificial intelligence, firm growth, and product innovation. Journal of Financial Economics, 147(2), 480–506. https://doi.org/10.1016/j.jfineco.2022.05.009 Bahoo, S., Cucculelli, M., Goga, X., & Mondolo, J. (2024). Artificial intelligence in finance: A comprehensive review through bibliometric and content analysis. SN Business & Economics, 4, 23. https://doi.org/10.1007/s43546-023-00618-x (Springer) Chen, M. A., Wu, Q., & Yang, B. (2019). How valuable is FinTech innovation? Review of Financial Studies, 32(5), 2062–2106. https://doi.org/10.1093/rfs/hhy130 Cui, J. (2025). The impact of AI technology on cross-border trade in Southeast Asia: A meta-analytic approach. arXiv. https://doi.org/10.48550/arXiv.2503.13529 (arXiv) Frost, J., Gambacorta, L., Huang, Y., Shin, H. S., & Zbinden, P. (2019). BigTech and the changing structure of financial intermediation. Economic Policy, 34(100), 761–799. https://doi.org/10.1093/epolic/eiaa003 Fuster, A., Goldsmith-Pinkham, P., Ramadorai, T., & Walther, A. (2022). Predictably unequal? The effects of machine learning on credit markets. Journal of Finance, 77(1), 5–47. https://doi.org/10.1111/jofi.13090 Goldstein, I., Jiang, W., & Karolyi, G. A. (2019). To FinTech and beyond. Review of Financial Studies, 32(5), 1647–1661. https://doi.org/10.1093/rfs/hhz025 Gomber, P., Koch, J.-A., & Siering, M. (2018). Digital finance and FinTech: Current research and future research directions. Journal of Business Economics, 87(5), 537–580. https://doi.org/10.1007/s11573-017-0852-x Haddad, C., & Hornuf, L. (2019). The emergence of the global FinTech market. Small Business Economics, 53(1), 81–105. https://doi.org/10.1007/s11187-018-9991-x Jagtiani, J., & Lemieux, C. (2018). Do FinTech lenders penetrate areas that are underserved by traditional banks? Journal of Economics and Business, 100, 43–54. https://doi.org/10.1016/j.jeconbus.2018.03.001 Khalil, M. A., Padmanabhan, R., Hadid, M., Elomri, A., & Kerbache, L. (2025). AI-driven transformation in trade finance: A roadmap for automating letter of credit document examination. Digital Business, 5(2), 100130. https://doi.org/10.1016/j.digbus.2025.100130 (ScienceDirect) Lee, I., & Shin, Y. J. (2018). FinTech: Ecosystem, business models, investment decisions, and challenges. Business Horizons, 61(1), 35–46. https://doi.org/10.1016/j.bushor.2017.09.003 Lu, S., Liang, S., Xue, Q., & Bian, H. (2024). Enhancing cross-border payments: The convergence of AI and blockchain for currency exchange optimization. Applied and Computational Engineering, 75, 160–165. https://doi.org/10.54254/2755-2721/75/20240531 (EWA Direct) Najem, R., Bahnasse, A., Amr, M. F., et al. (2025). Advanced AI and big data techniques in E-finance: A comprehensive survey. Discover Artificial Intelligence, 5, 102. https://doi.org/10.1007/s44163-025-00365-y (Springer) Ozturk, O. (2024). The impact of AI on international trade: Opportunities and challenges. Economics, 12(11), 298. https://doi.org/10.3390/economy12110298 (MDPI) Philippon, T. (2016). The FinTech opportunity. Journal of Economic Perspectives, 30(2), 179–200. https://doi.org/10.1257/jep.30.2.179 Rafiq-uz-Zaman, M. (2022). Redesign for 21st-Century Skills: Preparing Learners for a Rapidly Changing Workforce. Journal of Business Insight and Innovation, 1(2), 89–102. Retrieved from https://insightfuljournals.com/index.php/JBII/article/view/58 Rafiq-uz-Zaman, M. (2025). Between Adoption and Ambiguity: Navigating the AI Policy Vacuum in Pakistani Higher Education. Research Journal for Social Affairs, 3(6), 877-885. https://doi.org/10.71317/RJSA.003.06.0523 Rafiq-uz-Zaman, M. (2025). Use of Artificial Intelligence in School Management: A Contemporary Need of School Education System in Punjab (Pakistan). Journal of Asian Development Studies, 14(2), 1984-2009. https://doi.org/10.62345/jads.2025.14.2.56 Ruqnuzzaman, M. (2025). Explainable AI and blockchain for dual-currency payments. Research Square. https://doi.org/10.21203/rs.8004820/v1 (Research Square) Saqib, H. M., & Amin, H. (2026). Comparative analysis of AI regulation for FinTech cybersecurity and privacy in the EU and Qatar. Discover Artificial Intelligence, 6, 59. https://doi.org/10.1007/s44163-025-00736-5 (Springer) Thakor, A. V. (2020). FinTech and banking: What do we know? Journal of Financial Intermediation, 41, 100833. https://doi.org/10.1016/j.jfi.2019.100833 Upputuri, V. (2025). The future of international transactions: How AI is transforming cross-border payments. International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 11(1), 1515–1523. https://doi.org/10.32628/CSEIT251112157 (IJ of Scientific Research in CS) Vives, X. (2019). Digital disruption in banking. Annual Review of Financial Economics, 11, 243–272. https://doi.org/10.1146/annurev-financial-100719-120854 Zetzsche, D. A., Buckley, R. P., Arner, D. W., & Barberis, J. N. (2017). RegTech: The next generation of financial regulation. Georgetown Journal of International Law, 48, 593–678. https://doi.org/10.2139/ssrn.3047803